Resources and activities of occupational health service units in Poland. An analysis of the mandatory medical reporting for 2014-2018 - Andrzej Marcinkiewicz (Nofer Institute of Occupational Medicine, 2020)
Background The number and activities of occupational medicine physicians and occupational health service (OHS) units can be determined on the basis of obligatory medical reporting. Material and Methods The paper covers an analysis of the MZ-35 and MZ-35A statistical forms dated 2014-2018. In order to assess the scope of medical reporting, an online questionnaire survey among occupational medicine experts was performed. Results the scope of medical reporting, an online questionnaire survey among occupational medicine experts was performed. Results: There were 6685 occupational medicine physicians, 6005 basic OHS units and 20 regional occupational health centers (ROHC) registered in Poland in 2018. Certain regional differences in access to OHS can be noticed. On average, there were 3481 persons of productive age per 1 occupational medicine physician. On average, in 2014-2018, 5 223 000 prophylactic examinations of workers were performed annually, along with 322 000 examinations (also annually) related to the practical vocational training of pupils, students, participants in qualification vocational training and Ph.D. candidates. For the first time in history, in 2018 more preliminary than periodic examinations were performed. Every year, approximately 0.03% of the medical certificates regarding the existence or lack of medical contraindications to perform work, which are issued by basic OHS units, are being questioned by either employees or employers. In 58% of such cases, the initial decision was changed as a result of an appeal procedure in ROHC. The duty to submit an annual report regarding prophylactic praactivities has been obeyed by <60% of the obliged physicians in the recent 2 years. Among the most important reasons for such a situation, the implementation of online reporting, a lack of real consequences for not submitting the report, and a poor knowledge of said reporting among physicians were mentioned. Conclusions It is necessary to monitor, on the regional level, the availability of prophylactic care provided by OHS physicians, both for all employers obliged to provide such care and for all employees obliged to undergo medical examinations. The scope of obligatory public statistics reporting regarding OHS activities needs updates. Due to a relatively stable situation in relation to the types of issued certificates, it should be less detailed. Med Pr. 2020;71(4):429-40